Algorithmic trading, what if it is just an illusion? Evidence from experimental asset markets - Jacob-Leal, Sandrine; Hanaki, Nobuyuki (Journal of behavioral and experimental economics, 2024)
We experimentally investigate whether and how the potential presence of algorithmic trading (AT) in human-only asset markets can influence humans’ price forecasts, trading activities and price dynamics. Two trading strategies commonly employed by high-frequency traders, spoofing (SP) - associated with market manipulation - and market making (MM) - seen as liquidity provision - are considered. These experiments reveal that, first, the mere expectation of SP traders can, at first, impair price convergence towards fundamentals. Second, the expected presence of AT, especially MM traders, induce larger initial price forecasts deviations from fundamentals. Third, despite the absence of AT in our experiments, the information about the presence of AT, employing MM strategy, is sufficient to alter subjects trading behavior over time and the impact of past realized prices on subjects’ order prices. •Indirect effects of algorithmic trading (AT) analyzed in human-only markets.•Use of typical AT strategies employed in real markets: spoofing and market making.•Spoofing threat can impair at first price convergence towards fundamentals.•Prices are initially expected to be less informative due to AT expected presence.•Human trading behavior depends on AT expected presence and AT strategy type.